Achieving procurement cost efficiencies in a New Zealand telecommunication company : an exploratory study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Logistics and Supply Chain Management at Massey University, Palmerston North, New Zealand - Ravi, Jayshree (Massey University, 2010)
The purchasing function in supply chain management contributes directly to the operating results and profitability of an organization. The fact that purchasing spend of an organisation is over half of its revenue highlights its potential. Supply Chain Management addresses many aspects of a business, and it can be even more complex for a telecommunication organisation where both goods and services play a key role. This research utilised a single case study to investigate pathways to achieving procurement cost efficiencies. The current supply chain literature was used to assess the supply chain of a telecommunication organisation with a view to quickly identify opportunities for improvement. The research explored a number of topics as described below. • The processes in the procurement cycle, namely Forecast, Source, Order, Pay and Review. This was used to assess the procurement process maturity and recommendations for improvement were made. • Understanding the procurement spend is a key requirement for the development of a procurement strategy. This is typically performed by category. However this is a difficult task for most organisations. This study showed how a spend analysis and category management system can be designed and implemented. It also showed how this can be used in conjunction with a purchasing portfolio matrix to quickly focus on spend categories that would provide maximum benefit. • Research has shown that Information technology is a key enabler in the supply chain. This study also highlighted how the current SAP ERP system and E-procurement can be leveraged in the current context to obtain process and cost benefits. • Measurement of procurement performance is an important aspect for any process improvement exercise. The study identified relevant performance measures for supplier as well as payment performance. ii • The research also showed how the SCOR model can be used to provide an overview of the supply chain and the importance of calculating some key SCOR metrics to assess opportunities for improvements. The study revealed that a number of options are available for procurement cost reduction. It also highlights the importance of process compliance and integration with other aspects of the supply chain (especially forecasting) to exploit opportunities for cost reduction.
Keywords: Procurement cost efficiencies; Supply chain management; Telecommunications companies